228k views
2 votes
What is the simplified expression for the expression below?

-1(2x + 3) – 2(x - 1)
4x + 1
4x -2
ooo
4x+2
4x
-
1

User Arabam
by
5.6k points

2 Answers

4 votes

Answer:

-4x-1

Explanation:

-1(2x+3)-2(x-1)

-2x-3-2x+2

-2x-2x-3+2

-4x-3+2

-4x-1

User Uberwach
by
6.5k points
7 votes

Answer:

-4x - 1

Explanation:


-1(2x+3)-2(x-1)\qquad\text{use the distributive property}\\\\=(-1)(2x)+(-1)(3)+(-2)(x)+(-2)(-1)\\\\=-2x-3-2x+2\qquad\text{combine like terms}\\\\=(-2x-2x)+(-3+2)\\\\=-4x-1

User Cogslave
by
6.1k points